1999
DOI: 10.1002/1531-8249(199903)45:3<320::aid-ana7>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical features of mtDNA 14484 (ND6/m64V) point mutation associated with Leber's hereditary optic neuropathy

Abstract: We report the effect on complex I function of the 14484 Leber's hereditary optic neuropathy (LHON) mutation affecting the ND6 subunit gene. The same gene was also reported to carry another mutation, at position 14459, associated with the LHON/dystonia phenotype that induces a reduction of complex I–specific activity and increases the sensitivity to the product decylubiquinol. Given the proximity of both mutations in the ND6 gene, we tested the specific activity of complex I and its sensitivity to myxothiazol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
61
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 38 publications
7
61
1
Order By: Relevance
“…At low altitude the 3394C variant increases the risk of LHON (14)(15)(16)(17)(18), which is consistent with its 15-28% reduction in complex I-specific activity and a 7-17% reduction in maximum respiration rate.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…At low altitude the 3394C variant increases the risk of LHON (14)(15)(16)(17)(18), which is consistent with its 15-28% reduction in complex I-specific activity and a 7-17% reduction in maximum respiration rate.…”
Section: Discussionsupporting
confidence: 68%
“…The ND6 14459A mutation generates the most severe complex I defect (12) and causes LHON when heteroplasmic but dystonia when homoplasmic (11,13). The remaining mutations cause milder complex I defects (14)(15)(16)(17)(18) and cause LHON when near homoplasmic (8)(9)(10). For the milder LHON mutations (11778A, 3460A, 14484C) the penetrance of blindness is increased when the mutations arise on mtDNA haplogroup J (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…21 The pathogeni- European Journal of Human Genetics ND6 mutation and MELAS syndrome K Ravn et alcity of the previously reported 14484T?C and 14459G?A mutations is widely recognised and the effect of these mutations on the actitivity of complex I has been extensively studied. 22,23 The 14484T?C (M64V) mutation significantly increases the sensitivity of complex I to inhibitors binding to the ubiquinone site 22 and studies of transmitochondrial cybrids have shown that the 14459G?A mutation causes a drastic reduction in the actitivity of complex I. 23 The isolated decrease in complex I activity observed in our patient strongly suggests that the 14453G?A (A74V) mutation has the same effect on the ND6 polypeptide as the 14459G?A mutation (A72V), considering the identical amino acid changes and the close proximity of the two altered amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…LHON is due to a massive acute or subacute retinal ganglion cell death, characteristically leading to central vision loss (2)(3)(4). These pathogenic mutations invariably affect complex I subunits, which possibly interact with the quinone substrate (9,10), and a combination of partial respiratory deficiency and increased oxidative stress is documented to be the pathological consequence in transmitochondrial cell systems (11)(12)(13)(14)(15). However, the mtDNA pathogenic mutations are a necessary, but not sufficient, condition to actually develop LHON, as suggested by the variable penetrance (2,16).…”
mentioning
confidence: 99%